An application of procedural justice to stakeholder perspectives: examining police legitimacy and public trust in police complaints systems - Schulenberg, Jennifer L. (Policing and society, 2017)
Considerable research focuses on the complainant experience with civilian oversight agencies but we know much less about the perceptions of divergent stakeholders on the fairness in quality of decision-making and treatment associated with investigating allegations of police misconduct. Over 150 members of the community, law enforcement, and policy-makers were brought together to collaboratively develop recommendations to improve the transparency, accessibility, and accountability of a Canadian police complaints system (PCS). Using participant observation and survey data, the findings suggest the majority of participants hold negative views due to underlying themes of distrust in the investigation process, a reluctance to report due to inadequate knowledge and a fear of police reprisals, particularly by high risk and marginalised populations. Stakeholder confidence cannot be separated from the principles of procedural justice and due process constraints. Views on the legitimacy of both the police and the PCS are shaped by the absence of procedural justice principles of fairness in treatment and decision-making. Further, citizens appear to confound perceptions of legitimacy of the PCS with that of behaviour during police-citizen encounters. Thus, to increase public confidence the PCSs must work with police services to improve relationships with the community by developing initiatives that target the elements of the procedural justice model separately.